Effect of chitosan edible films added with Thymus moroderi and Thymus piperella essential oil on shelf-life of cooked cured ham - Ruiz-Navajas, Y. (J Food Sci Technol, 2015)
The aim of this work was to develop chitosan edible films added with essential oils obtained from two Thymus species, Thymus moroderi (TMEO) and Thymus piperella (TPEO) to determine their application for enhancing safety (antioxidant and antibacterial properties) and shelf-life of cooked cured ham (CCH) stored at 4 °C during 21 days. Addition of TMEO and TPEO into chitosan films decreased the aerobic mesophilic bacteria (AMB) and lactic acid bacteria (LAB) counts in coated cooked cured ham samples as compared with uncoated samples. Both AMB and LAB showed the lowest counts in CCH samples coated with chitosan films added with TPEO at 2 %. In regard to lipid oxidation, the CCH samples coated with chitosan films added with TMEO or TPEO had lower degrees of lipid oxidation than uncoated control samples. Chitosan films added with TPEO at 2 % showed the lowest values. The addition of TPEO or TMEO in chitosan films used as coated in CCH improved their shelf life.